2015
DOI: 10.1007/s13277-015-3455-6
|View full text |Cite
|
Sign up to set email alerts
|

γ-Synuclein confers both pro-invasive and doxorubicin-mediated pro-apoptotic properties to the colon adenocarcinoma LS 174T cell line

Abstract: γ-synuclein, a neuronal protein of the synuclein family, is involved in carcinogenesis. To investigate its role in colorectal cancer carcinogenesis, we overexpressed γ-synuclein in LS 174T colon adenocarcinoma cell line (termed LS 174T-γsyn). When compared with untransfected/mock transfectants, LS 174T-γsyn had higher mobility in scratch wound assay, tend to scatter more in cell-scattering assay, and had enhanced lamellipodia and filopodia formation in cell-spreading assay. Enhanced adhesion of LS 174T-γsyn to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
(57 reference statements)
4
8
0
Order By: Relevance
“…Western blot confirmed the overexpression of γ-Syn and PrP C in LS 174T-γ-Syn and LS 174T-PrP cells, respectively, as established previously (Chieng & Say, 2015;Goh & Say, 2015) ( Figure 1 A&B, respectively). MTT proliferation assay was then carried out to evaluate the effects of LS 174T CM on EA proliferation rate and to determine the optimal treatment duration for the rest of the study ( Figure 1C).…”
Section: T-prp CM Reduce Ea Telomerase Activitysupporting
confidence: 84%
See 3 more Smart Citations
“…Western blot confirmed the overexpression of γ-Syn and PrP C in LS 174T-γ-Syn and LS 174T-PrP cells, respectively, as established previously (Chieng & Say, 2015;Goh & Say, 2015) ( Figure 1 A&B, respectively). MTT proliferation assay was then carried out to evaluate the effects of LS 174T CM on EA proliferation rate and to determine the optimal treatment duration for the rest of the study ( Figure 1C).…”
Section: T-prp CM Reduce Ea Telomerase Activitysupporting
confidence: 84%
“…All cell lines have been checked to ensure they are free of contamination and have been used from young stock (less than 7 passages). LS 174T overexpressing γ-Syn (LS 174T-γ-Syn) and PrP (LS 174T-PrP) were previously established in our laboratory (Chieng & Say, 2015;Goh & Say, 2015), and overexpression of γ-Syn and PrP C in LS 174T cells was confirmed once again in this study by Western blotting, as detailed previously (Chieng & Say, 2015;Goh & Say, 2015). In this study, untransfected LS 174T, LS…”
Section: Cell Culture and Treatmentssupporting
confidence: 62%
See 2 more Smart Citations
“…In addition to inflammation and stress responses, p38 is involved in the control of cell cycle and proliferation [ 13 ]. Previous studies have indicated the reciprocal regulation of HGF and activated p38 in cell proliferation [ 14 – 16 ]. Transforming growth factor- β (TGF- β ) downregulated activation of HGF precursors and influenced hepatocyte plasticity via p38 signal pathway [ 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%